Analysis of Bistatic Scattering of Electromagnetic Waves by Melting Layer - Jha, Binay Kumar (Himalayan Physics, 2011)
In this communication bistatic scattering of electromagnetic waves by the melting layer of precipitation has been presented. The bistatic radar reflectivities have been formulated and can be computed at 1- 100GHz by applying the Mie theory for raindropsize distributions at rain rates below 12.5mm/h. It is very important to study the integrated interference effects all along the propagation path as well as of greatest interest for evaluating the impact of the melting layer effects on bistatic interference for communications. Key words: Bistatic scattering; Interference; Hydrometeors; Melting layer The Himalayan Physics Vol.1, No.1, May, 2010 Page: 41-43 Uploaded Date: 28 July, 2011